The Distribution of Mutans Streptococci in Plaque on the margin of Amalgam, on the Enamel, and on the Surface of Amalgam Restoration - Soeherwin Mangundjaja; Abdul Muthalib; Ariadna Djais; Elza Ibrahim Auerkari (Faculty of Dentistry, Universitas Indonesia, 2015)
The aim of the study was to evaluate the level of distribution of mutans streptococci on the margin of amalgam restoration, compared with that on the enamel and on the surface of restoration. It is assumed that the level of distribution of mutans streptococci on the margin will be able to influence the presence of secondary caries. In this study the first molars of 20 patients were treated with amalgam restoration. The mutans streptococci was measured as the percentage of total CFU count in the plaque. The results showed a mean count of 108.8 (SD= 55.2) of mutans streptococci in the margin; 97.7 (SD=63.5) on the enamel; and 61.4 (SD=32.4) on the surface of amalgam restoration. It seems that the level of mutans streptococci on the margin is higher than those on the enamel (p=0.006) as well as higher than those on the surface of (p=0.031). It is suggested that elevated level of mutans streptococci on the margin can indicate risk to secondary caries.